(untitled) (Global Business Management Review (GBMR), 2022)
Albert J. Mills (Professor Management) is Director of the PhD program at Saint Mary University (Nova Scotia Canada). Mills interest in knowledge has lead him to exploration of management education and the role of research strategies including historiography, case study, and post positivistic research methods. He served as an active researcher and executive member of several research organizations. He is the Editorial board member of Qualitative research in management and education, Management and Organizational History. He is engaged in a series of ongoing case studies of airline companies and histories of management thought and scholarly associations in North America. Gabrielle Durepos is an Assistant Professor at St. Francis Xavier University in Nova Scotia, Canada, where she teaches organizational behavior. Her research interests are far ranging and include history, historiography, the sociology of knowledge, epistemology, knowledge, organizational ethics etc. Durepos has published her work in peer reviewed journals, including, Management and Organizational History, and Journal of Management History. Elden Wiebe is an Associate Professor of business, department of management and commerce, The King’s University College, Edmonton, Alberta, Canada. Weibe’s recent work has combined his interests in organizational change and time. His initial work with colleagues has been published in the Journal of Management Inquiry. Wiebe is a member of the Academy of Management, and the Administrative Science Association of Canada.